Association of Toll-Like Receptor 4 Gene Polymorphisms with Acute Aortic Dissection in a Chinese Han Population. (9th December 2020) - Li, Tan; Liu, Xiaozheng; Ning, Hongxia; Li, Xintong; Yang, Jun; Ma, Chunyan
Abstract : Background . Inflammation may be involved in the pathogenesis of acute aortic dissection (AAD). Toll-like receptor 4 ( TLR4 ) is known to play a critical role in regulating the immune and inflammatory processes. To date, the relationship between genetic variation of TLR4 and AAD is far from clear. The purpose of our study was to illustrate the relevance of TLR4 polymorphisms with the susceptibility to AAD. Methods . A total of 222 AAD patients and 222 controls were enrolled in this study. Frequency distributions of TLR4 polymorphisms (rs10759932 in the promoter and rs11536889 in the 3 ′ -untranslated region) were determined by the KASP method. Clinical parameters were acquired from subjects' medical records, and serum TLR4 levels were collected from our previously published data. Results . We found that rs10759932 polymorphism was associated with a reduced risk of AAD in the overall population (CC vs. TT: OR = 0.393, 95 % CI = 0.164 ‐ 0.939, P = 0.036 ; recessive model: OR = 0.439, 95 % CI = 0.196 ‐ 0.984, P = 0.045 ) and subgroup analyses stratified by sex. The GC genotype and dominant model of rs11536889 conferred a significantly higher risk of AAD compared with GG genotype in female subjects (GC vs. GG: OR = 3.382, 95 % CI = 1.051 ‐ 10.885, P = 0.041 ; dominant model: OR = 3.043, 95 % CI = 1.041 ‐ 8.900, P = 0.042 ). In addition, a significant interaction between the rs11536889 recessive model and dyslipidemia was observed for an increased risk of AAD (P interaction = 0.038, OR = 15.229 ) after the adjustment for potential clinical covariates. We also used the false-positive report probability (FPRP) analysis to validate the significant results. Furthermore, rs11536889 polymorphism could affect the maximal aortic diameters of AAD (P = 0.037 ), while AAD patients carrying CC genotype of rs10759932 showed lower serum TLR4 levels than TT genotype carriers (P = 0.043 ). Conclusions . Our findings provide evidence for the association between TLR4 polymorphisms and AAD susceptibility in a Chinese Han population, which may have some implications for understanding the role of TLR4 in the pathophysiology of AAD.